ANALISIS TINGKAT KEPUASAN NASABAH ATAS PELAYANAN PADA PT. BANK NEGARA INDONESIA (Persero) Tbk. CABANG PEKANBARU - Indrawati, Henny Indrawati Henny; Johan, Rina Selva Johan Selva (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: This study was conducted to analyze the quality level of customer satisfaction at PT. Bank Negara Indonesia (Persero) Tbk. Population of this study are customers of PT. Bank Negara Indinesia (Persero0 Tbk in 2014 amounting to 25.500 and 10% of the population sample of 100 respondents. The sampling based technique incidental. Data were collected through a questionnaire while using data analysis techniques importance performance analysis (IPA). The results showed that most customers are quite satisfied with the services given PT. Bank Negara Indonesia (Persero) Tbk. Seen from the results of testing the level of customers satisfaction with the method importance performance analysis (IPA) there are seven attributes that go into quadrant A ( top priority) which means considered important by customers but not maximum or unsatisfactory.Key words: Customers Satisfaction, Importance Performance Analysis (IPA)